Preliminary study to evaluate the phytochemicals and physiochemical properties in red and black date's vinegar. Issue 6 (29th April 2019) - Ali, Zeshan; Ma, Haile; Rashid, Muhammad Tayyab; Wali, Asif; Younas, Shoaib
Abstract: Antioxidant activity, total phenolic content (TPC), total flavonoids, carotenoids, pH, and total titratable acidity of red and black date's vinegar were analyzed. The extraction method was designed and optimized for this purpose with respect to the variety and solvent concentrations along with the time of ultrasonication. The results showed that red dates' vinegar has significantly ( p  < 0.05) higher total phenols (3.38 ± 0.13 mg GAE/ml) and antioxidant activity as compared to black dates' vinegar, which had a higher amount of carotenoids (3.43 ± 0.11 mg/100 ml). Similarly, red dates' vinegar has more flavonoids as compared to commercially available Zhenjiang vinegar. In terms of physiochemical properties, both red and black date's vinegar were not significantly different ( p  > 0.05). Use of 50% and 80% methanol with 25 min of ultrasonication for extraction seemed more effective. The total phenols, flavonoids, antioxidant activity, carotenoids, and physiochemical analysis of the red and black date's vinegar indicated that vinegar from dates (red or black dates) is a competitive product in the marketplace. Abstract : Antioxidant activity, total phenolic content (TPC), total flavonoids, carotenoids, pH, and total titratable acidity of red and black date's vinegar were analyzed. Extraction method was designed and optimized for this purpose with respect to the variety and solvent concentrations along with the time of ultrasonication. The results showed that red dates' vinegar has significantly ( p  < 0.05) higher total phenols (3.38 ± 0.13 mg GAE/ml) and antioxidant activity as compared to black dates' vinegar, which had a higher amount of carotenoids (3.43 ± 0.11 mg/100 ml).